Public schools and critical education: Alternative education policy in Indonesia - Rahmad Rafid; Riski Febria Nurita; Dedi Dores (Goodwood Publishing, 2025)
Purpose: This study analyzes the implementation of community school policies within the framework of critical education, based on Presidential Instruction No. 8 of 2025 on the eradication of extreme poverty. Research Methodology: This research uses qualitative methods based on policy studies to evaluate the effectiveness, challenges, and opportunities of community school programs in supporting poverty reduction through education. Results: “Sekolah Rakyat” can build critical awareness in poor communities, strengthen local participation, and integrate education with local wisdom. However, the success of this program still faces the challenges of inter-agency coordination, limited human resources, and inadequate facilities. Therefore, sustainable policy support, cross-sector collaboration, and community engagement are essential to strengthen the impact of Community Schools as a tool of social transformation and inclusive education. Conclusions: The implementation of